2017
DOI: 10.1590/1980-57642016dn11-020015
|View full text |Cite
|
Sign up to set email alerts
|

Catatonia, beyond a psychiatric syndrome

Abstract: Although catatonia is a well-known psychiatric syndrome, there are many possible systemic and neurological etiologies. The aim of this case report was to present a case of a patient with cerebral venous sinus thrombosis and infarction in which catatonia was the clinical manifestation of a possible nonconvulsive status epilepticus. To our knowledge, only one such case has been reported in the literature, which had a simplified diagnostic investigation. It is important to correctly recognize the organic cause un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
(30 reference statements)
0
8
0
1
Order By: Relevance
“…Catatonia is heterogeneous in presentation and cause. In this case, report, we describe the first case to our knowledge of catatonia associated with acute COVID-19 [4]. In our case, the cause could multifactorial either due to direct or indirect effect of covid-19.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Catatonia is heterogeneous in presentation and cause. In this case, report, we describe the first case to our knowledge of catatonia associated with acute COVID-19 [4]. In our case, the cause could multifactorial either due to direct or indirect effect of covid-19.…”
Section: Discussionmentioning
confidence: 63%
“…However, Due to this low level of awareness catatonia among general medical doctors is likely to be underdiagnosed which subject the patient to increased risk of morbidity and a potentially fatal outcome [3]. In view of infectious cause for catatonia, the pathogenesis is thought to be due to either a direct toxic effect of pathogen or an immune response [1,4]. Despite that Coronavirus disease 2019 (COVID-19) known to cause severe acute respiratory symptoms, surprisingly, there have been reports of neurologic symptoms [5].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, they reported that the cortico‐basal ganglia loop and cortico‐cortical circuit were impaired. Recent reports have also shown a correlation between nonconvulsive status epilepticus and catalepsy after stroke 7 …”
Section: Discussionmentioning
confidence: 94%
“…Some general medical conditions may also present with catatonic symptoms or place patients at a higher risk of catatonia, and several case reports have been published on the subject. These case reports include conditions such as hyponatremia, cerebral venous sinus thrombosis, and liver transplantation, among others [ 4 , 5 , 6 ]. Patients taking benzodiazepines or clozapine are also at risk of developing catatonia after withdrawal from these medications [ 7 ].…”
Section: Introductionmentioning
confidence: 99%